1998
DOI: 10.1097/00002060-199809000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Admission Balance and Outcomes of Patients Admitted for Acute Inpatient Rehabilitation1

Abstract: The objective of the study contained herein was to evaluate the clinical use of the Berg Balance Scale in a heterogeneous acute inpatient rehabilitation population and to assess the relationship between balance scores at admission and rehabilitation outcomes, including functional gain and length of stay. This was a prospective study of 45 patients with diagnoses including stroke (n = 15), traumatic brain injury (n = 19), and other impairments (n = 11) who were admitted for acute inpatient rehabilitation. Funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
1
7

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 10 publications
1
42
1
7
Order By: Relevance
“…So, at the dressing activity even with the balance compromised, the patient can perform this task lying down and not impeding this one to be performed. The ability of maximum leaning for both sides and forward and also the symmetrical sitting was not strongly correlated to the function 24 .…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…So, at the dressing activity even with the balance compromised, the patient can perform this task lying down and not impeding this one to be performed. The ability of maximum leaning for both sides and forward and also the symmetrical sitting was not strongly correlated to the function 24 .…”
Section: Discussionmentioning
confidence: 75%
“…However Nichols et al reported that even after two (2) weeks into intensive rehabilitation, there were no significant correlation between the postural control measures and FIM scores 24 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Duong and colleagues subsequently replicated this finding in a larger sample [5]. Several investigators have reported that early balance impairment predicts worse outcome at rehabilitation discharge [27][28][29]. Early residual motor impairment may also be associated with poorer vocational outcome after severe TBI.…”
Section: Discussionmentioning
confidence: 91%
“…Statik dengenin hastanede yat›fl süresi ve lokomotor fonksiyonla iliflkisi çeflitli çal›flmalarda araflt›r›lm›flt›r (9,21,(38)(39)(40)(41) Günlük yaflam aktivitelerinde; yürüme, transfer ve uzanma gibi aktivitelerin gerçeklefltirilebilmesi için oturma ve ayakta durma s›ras›nda dengenin korunmas› gereklidir. Gövde ve ekstremite kaslar› otomatik postüral cevaplar›n koordinasyonu ve regülasyonunda yer al›rlar.…”
Section: G Gi Ir Ri Ifl Flunclassified